Peningkatan Literasi Keuangan Ibu Rumah Tangga dalam Pengelolaan Anggaran Berbasis Skala Prioritas di Desa Pengkajoang - Farhan Dwinanda Hanisyahputra; Dwi Ayu Siti Hartinah H; Nila Sastrawaty; Dedi Harianto; Nabila Amelia Hanisyahputri (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2026)
Fluctuating global economic conditions directly impact household economic resilience, which is often exacerbated by low financial literacy and irregular spending patterns. This community service program aims to improve the financial literacy of housewives in Pengkajoang Village through priority-based budget management. The method of implementation of this activity is carried out through interactive socialization and education to groups of housewives. The material presented includes techniques for identifying the difference between needs and wants, preparing an effective household budget, and practical assistance in recording daily income and expenses using simple, applicable media. The results of this community service activity indicate an increase in participants' awareness and understanding of the strategic role of housewives as family financial managers. This is evidenced by the enthusiasm of participants in discussion sessions related to strategies for allocating emergency funds and efficiency of expenditure items amidst uncertain income. By internalizing the concept of priority scales, participants now have the life skills to conduct more measured financial planning to achieve financial independence and family economic resilience in Pengkajoang Village.